2015
DOI: 10.1371/journal.pone.0141256
|View full text |Cite
|
Sign up to set email alerts
|

Effects of High-Intensity Interval Training versus Continuous Training on Physical Fitness, Cardiovascular Function and Quality of Life in Heart Failure Patients

Abstract: IntroductionPhysical fitness is an important prognostic factor in heart failure (HF). To improve fitness, different types of exercise have been explored, with recent focus on high-intensity interval training (HIT). We comprehensively compared effects of HIT versus continuous training (CT) in HF patients NYHA II-III on physical fitness, cardiovascular function and structure, and quality of life, and hypothesize that HIT leads to superior improvements compared to CT.MethodsTwenty HF patients (male:female 19:1, 6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
116
2
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(122 citation statements)
references
References 61 publications
(88 reference statements)
3
116
2
1
Order By: Relevance
“…The authors of eight studies [9, 12, 1921, 25, 26, 32] involving 170 patients reported increased LVEF following INTERVAL and CONTINUOUS. A random-effects model showed no significant difference between groups (MD 2.18%, 95% CI −0.54% to 4.90%, p = 0.12).…”
Section: Resultsmentioning
confidence: 99%
“…The authors of eight studies [9, 12, 1921, 25, 26, 32] involving 170 patients reported increased LVEF following INTERVAL and CONTINUOUS. A random-effects model showed no significant difference between groups (MD 2.18%, 95% CI −0.54% to 4.90%, p = 0.12).…”
Section: Resultsmentioning
confidence: 99%
“…Twelve studies [5, 2837, 39] included a usual care control group, of these, two studies [5, 28] included two different aerobic intervention groups. One study [38] did not include a control group and only compared intervention groups undertaking different aerobic exercise protocols.…”
Section: Resultsmentioning
confidence: 99%
“…3 However, recently published data with regard to acute and chronic effects of high-intensity interval exercise are mixed with some data suggesting worsening of strain characteristics in otherwise healthy individuals 4,5 and no adverse changes in individuals with heart failure and reduced ejection fraction. 6,7 Given that the effects of HIIT on ventricular strain characteristics in patients with HFpEF remain unknown, we carried out secondary analyses to explore the effects of HIIT on biventricular strain characteristics.…”
Section: Introductionmentioning
confidence: 99%